Study the Effect of the Sugar Solutions on the Rotation of the Plane of Polarization - Matti, Dina J. (Nahrain University College of Engineering Journal, 2014)
This paper deals with studying theeffect of the polarization properties ofsucrose solution (sugar which isdissolved in distilled water) as an activematerial and proves the ability of thissolution to rotate the plane of polarizedlight that passes through it with an angle(?) which is called the angle ofrotation.Angle of rotation depends on themolecular structure, the concentration ofthe dissolved substance, the path lengthof the light that passes through thesolution,and the light wavelength. Themethod of measuring the transmittedpower and angle of rotation is called“optical activity”. Two types of lightsource are used. The first one was thexenon lamp and chooses three colorfrom it (red, green, and blue) using theproper filters, and the second source wasHe-Ne laser of wavelength 632nm. Ineach case, the rotation angle andtransmitted power were measured andthe specific angle of rotation wascalculated at different concentrations ofthe solution.The benefit of this work, as an opticallaboratory application to measure opticalproperties of various materials, includingcircular birefringence (optical rotation).It has been found that the effect ofpolarized solution on the rotation angleswas very large for blue light whencomparing with red, because of thesemeasured angles depends on increasingpolarized solution concentrations anddue to the short wavelength of blue lightwith respect to green and red lights.